Reduced Levels of miR-145-3p Drive Cell Cycle Progression in Advanced High-Grade Serous Ovarian Cancer - Eva González-Cantó; Mariana Monteiro; Cristina Aghababyan; Ana Ferrero-Micó; Sergio Navarro-Serna; Maravillas Mellado-López; Sarai Tomás-Pérez; Juan Sandoval; Antoni Llueca; Alejandro Herreros-Pomares; Juan Gilabert-Estellés; Vicente Pérez-García; et al. (Cells)
High-grade serous ovarian cancer (HGSOC) is the most lethal form of gynecologic cancer, with limited treatment options and a poor prognosis. Epigenetic factors, such as microRNAs (miRNAs) and DNA methylation, play pivotal roles in cancer progression, yet their specific contributions to HGSOC remain insufficiently understood. In this study, we performed comprehensive high-throughput analyses to identify dysregulated miRNAs in HGSOC and investigate their epigenetic regulation. Analysis of tissue samples from advanced-stage HGSOC patients revealed 20 differentially expressed miRNAs, 11 of which were corroborated via RT-qPCR in patient samples and cancer cell lines. Among these, miR-145-3p was consistently downregulated post-neoadjuvant therapy and was able to distinguish tumoural from control tissues. Further investigation confirmed that DNA methylation controls MIR145 expression. Functional assays showed that overexpression of miR-145-3p significantly reduced cell migration and induced G0/G1 cell cycle arrest by modulating the cyclin D1-CDK4/6 pathway. These findings suggest that miR-145-3p downregulation enhances cell proliferation and motility in HGSOC, implicating its restoration as a potential therapeutic target focused on G1/S phase regulation in the treatment of HGSOC.